Exploring the Outcomes That Matter Most to Young People Treated for Chronic Pain: A Qualitative Study - Rhiannon Joslin; Maggie Donovan-Hall; Lisa Roberts (Children, 2021)
Global and national policies state that all children and young people should be part of decision making and that outcomes that matter to them should take priority, yet patient-centred outcomes have been identified as a gap in the paediatric chronic pain literature. This study gave youths experiencing chronic pain a platform to have their views heard. Using novel methods, twenty-one young people, aged 11 to 18 years old, completed a semi-structured interview in which they constructed a timeline drawing to symbolise their treatment. They identified when aspects of their life changed (outcomes) and described the importance of these changes. Thematic analysis identified four themes that emerged at different stages of the treatment: “perfect storm”; “turning points”; “disconnect”; and; “free”. “Turning points” were points in time when the narrative of the young person took a turn in a different direction. At these points, the outcomes important to them also changed. Youths initially prioritised outcomes related to pain, then during treatment the focus became their emotional functioning, with role functioning and “going out” becoming the focus at the end. The stage of treatment as perceived by the young person impacted which outcomes mattered most.